Pengaruh Indeks Pembangunan Manusia dan Tingkat Pengangguran Terbuka Terhadap Jumlah Penduduk Miskin di Provinsi Aceh Tahun 2010-2022 - Jesaya Kemalementa Karo-Karo; Jesika Jesika; Sena Samosir; Silvia Agustin Manullang; Eko Wahyu Nugrahadi (CV. Ulil Albab Corp, 2024)
The purpose of this study is to determine and demonstrate how much the HDI and TPT affect the poverty rates in Aceh Province between 2010 and 2022. Using the Eviews 10 software program, a linear multiple analysis method was employed in this study to ascertain the impact of the independent variable on the dependent variable. Series data for the years 2010–2022 are used. The study's findings indicate that there is a substantial correlation between the HDI and poverty variables, with the former having a negative impact. In the meantime, there is a noteworthy correlation and a positive impact of the TPT variable on the poverty variable. Independent variables, such as the Human Development Index (HDI) and Open Unemployment Rate (TPT) variables, influence 82.92% of the dependent variable, which is poverty; additional variables not covered in this study influence the remaining 17.8%.